ANALYSIS OF CONTEXT DATA IN THE REGIONAL MONITORING OF KNOWLEDGE QUALITY - Melnik, Valentin; Vanin, Aleksandr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Ensuring high quality education is an important priority of state educational policy in the Russian Federation. Recently, the quality of education, which directly depends on many factors, has been widely discussed. The aim of the study is a statistical analysis of the results of regional qualimetric monitoring of the quality of knowledge based on contextual indicators that affect the educational results of students. As the main tools used correlation and regression analysis. The described technique was tested in the Pskov region. The results of the study provide relevant information to all interested parties: state and municipal levels of education management, heads and teachers of educational institutions, parents and students.